RING‐box proteins regulate leaf senescence and stomatal closure via repression of ABA transporter gene ABCG40. Issue 5 (28th April 2022) - Wei, Yun Qi; Yuan, Jun Jie; Xiao, Chen Chen; Li, Gui Xin; Yan, Jing Ying; Zheng, Shao Jian; Ding, Zhong Jie
ABSTRACT: Plant hormone abscisic acid (ABA) plays an indispensable role in the control of leaf senescence, during which ABA signaling depends on its biosynthesis. Nevertheless, the role of ABA transport in leaf senescence remains unknown. Here, we identified two novel RING‐box protein‐encoding genes UBIQUITIN LIGASE of SENESCENCE 1 and 2 ( ULS1 and ULS2 ) involved in leaf senescence. Lack of ULS1 and ULS2 accelerates leaf senescence, which is specifically promoted by ABA treatment. Furthermore, the expression of senescence‐related genes is significantly affected in mature leaves of uls1/uls2 double mutant (versus wild type (WT)) in an ABA‐dependent manner, and the ABA content is substantially increased. ULS1 and ULS2 are mainly expressed in the guard cells and aging leaves, and the expression is induced by ABA. Further RNA‐seq and quantitative proteomics of ubiquitination reveal that ABA transporter ABCG40 is highly expressed in uls1/uls2 mutant versus WT, though it is not the direct target of ULS1/2. Finally, we show that the acceleration of leaf senescence, the increase of leaf ABA content, and the promotion of stomatal closure in uls1/usl2 mutant are suppressed by abcg40 loss‐of‐function mutation. These results indicate that ULS1 and ULS2 function in feedback inhibition of ABCG40‐dependent ABA transport during ABA‐induced leaf senescence and stomatal closure. Abstract : The RING‐box proteins UBIQUITIN LIGASE of SENESCENCE 1 and 2 function in feedback inhibition of ABCG40‐dependent abscisic acid (ABA) transport during ABA‐induced leaf senescence and stomatal closure.